2021
DOI: 10.7759/cureus.15309
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Trends of Opioid Use in Patients With Depression in the United States

Abstract: BackgroundDepression and prescription opioid use have a bi-directional relationship. Depression commonly co-occurs with chronic noncancer pain and is known to be associated with opioid use. Studies have found an increased risk of depression only in patients with opioid dependence. Other studies have found an increased risk of opioid misuse in depressed patients. In addition, chronic pain conditions can lead to depression without the use of opioids. MethodsWe used the National Health and Nutrition Examination S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…This result is partially consistent with Jamison et al, who reported that 40% of chronic pain patients treated with opioids suffer from additional affective disorders (depression and anxiety), which in turn are associated with a significantly increased misuse of opioids [36]. There are a number of studies demonstrating that people with psychological comorbidities such as depression and anxiety are prevalent among patients with chronic non-cancer pain [6,[48][49][50], and that they are more likely to receive long-term opioid therapy for non-cancer pain than those without such comorbidities [4]. One reason for that could be that mental health conditions and chronic non-cancer pain are closely correlated concerning severity [5].…”
Section: Discussionsupporting
confidence: 84%
“…This result is partially consistent with Jamison et al, who reported that 40% of chronic pain patients treated with opioids suffer from additional affective disorders (depression and anxiety), which in turn are associated with a significantly increased misuse of opioids [36]. There are a number of studies demonstrating that people with psychological comorbidities such as depression and anxiety are prevalent among patients with chronic non-cancer pain [6,[48][49][50], and that they are more likely to receive long-term opioid therapy for non-cancer pain than those without such comorbidities [4]. One reason for that could be that mental health conditions and chronic non-cancer pain are closely correlated concerning severity [5].…”
Section: Discussionsupporting
confidence: 84%
“…The single variable most significantly associated with the prevalence of OUD, even after correcting for other variables in multivariate analysis, was the estimated prevalence of depression. This finding is consistent with the conceptualization of the opioid crisis as being related to "despair" [12], with research in individuals showing that significant depressive symptoms are a robust predictor of opioid misuse [40][41][42], and with the bidirectional association between depression and opioid misuse [48]. At a more fundamental level, there appear to be genetic and neurobiological links between depression and opioid dependence [49,50].…”
Section: Discussionsupporting
confidence: 84%
“…58 In the United States population-based study NHANES data sets (2005/2006 to 2017/2018 cycles, mean age 46.5 years), the prevalence of narcotics use (primarily opioids) was 6%. 59 Narcotics use was more than threefold greater, 17.2% in the depressed group vs 5.0% in the nondepressed group. 59 The general patterns from these diverse studies 3,56,57,59 highlight the strong dependence of illicit substance use on age, and the increased risk of illicit substance use in males and in individuals with depression.…”
Section: Activementioning
confidence: 89%
“…The prevalence of depression in the United States increased between 2015‐2019, and in 2020, the prevalence in young adults (18‐25 years) and in adolescents (12‐17 years) was around 17% 58 . In the United States population‐based study NHANES data sets (2005/2006 to 2017/2018 cycles, mean age 46.5 years), the prevalence of narcotics use (primarily opioids) was 6% 59 . Narcotics use was more than threefold greater, 17.2% in the depressed group vs 5.0% in the nondepressed group 59 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation